Investigating the feasibility and effectiveness of bacterial culture in negative pressure wound drainage fluid - Wu, Junjie; Chang, Zhengqi (Frontiers in Medicine, 2024)
Purpose: To analyze the feasibility and effectiveness of bacterial culture in negative pressure wound drainage(NPWD) fluid in patients with Pyogenic Vertebral Osteomyelitis (PVO). Methods: A retrospective analysis was performed on 17 patients with PVO who were treated with negative pressure drainage at the Department of Orthopedics in our hospital from January 1, 2018 to December 31, 2021. Data was obtained while the patients were in the hospital, including 12 males and 5 females with an average age of 57.71±9.93 years. After applying the negative pressure drainage technique, the drainage fluid was collected and a bacterial culture was performed. The positive rate of bacterial culture in the drainage fluid was recorded. Comparing the positive rate of specimen culture obtained by this surgical method with other methods reported in the literature, the effectiveness of negative pressure drainage in the treatment of PVO was analyzed. Results: All patients were placed with negative pressure sponge during operation and underwent continuous negative pressure aspiration after operation. The average of total drainage volume was 186.47 ±29.44ml. The drainage fluid was successfully retained for bacterial culture, and the results of bacterial culture were negative in 3 patients. Pathogenic bacteria were successfully obtained from negative pressure drainage fluid in 14 cases, with a positive rate of 82.4% (14/17). Conclusions: Using negative pressure drainage to retain drainage fluid for bacterial culture can significantly increase the positive rate, which is helpful for the diagnosis of PVO and rational antibiotic treatment.